2022
DOI: 10.3846/ijspm.2022.16834
|View full text |Cite
|
Sign up to set email alerts
|

Pass-Through Business Entity Choice and Earnings Management: Evidence From Uk Real Estate Investment Trust Conversion

Abstract: This empirical study innovatively investigates how the choice of a pass-through business entity and corresponding regulatory regime influence firms’ earnings management (EM) behaviors by testing on the UK Real Estate Investment Trust (REIT) conversion. A substantial proportion of UK non-REIT publicly traded property companies (LPCs) have chosen to become REITs since the UK REITs were launched in 2007. We conduct a series of tests on a database containing UK LPCs and REITs from 2000 to 2019 and find that conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Further studies on earnings management in real estate firms could investigate whether firms engage more strongly in real activities manipulation than in accrual accounting. While Anglin et al (2013) discovered this to be the case among REITs, both Deng and Ong (2018) and Liang et al (2022)…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Further studies on earnings management in real estate firms could investigate whether firms engage more strongly in real activities manipulation than in accrual accounting. While Anglin et al (2013) discovered this to be the case among REITs, both Deng and Ong (2018) and Liang et al (2022)…”
Section: Discussionmentioning
confidence: 97%
“…While Anglin et al. (2013) discovered this to be the case among REITs, both Deng and Ong (2018) and Liang et al. (2022) found that REITs tend to engage in more real earnings management instead of accrual earnings management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations